Consensus-based care recommendations for adults with myotonic dystrophy type 1. Issue 6 (December 2018) - Ashizawa, Tetsuo; Gagnon, Cynthia; Groh, William J.; Gutmann, Laurie; Johnson, Nicholas E.; Meola, Giovanni; Moxley, Richard; Pandya, Shree; Rogers, Mark T.; Simpson, Ericka; Angeard, Nathalie; Bassez, Guillaume; et al.
Abstract : Purpose of review: Myotonic dystrophy type 1 (DM1) is a severe, progressive genetic disease that affects between 1 in 3, 000 and 8, 000 individuals globally. No evidence-based guideline exists to inform the care of these patients, and most do not have access to multidisciplinary care centers staffed by experienced professionals, creating a clinical care deficit. Recent findings: The Myotonic Dystrophy Foundation (MDF) recruited 66 international clinicians experienced in DM1 patient care to develop consensus-based care recommendations. MDF created a 2-step methodology for the project using elements of the Single Text Procedure and the Nominal Group Technique. The process generated a 4-page Quick Reference Guide and a comprehensive, 55-page document that provides clinical care recommendations for 19 discrete body systems and/or care considerations. Summary: The resulting recommendations are intended to help standardize and elevate care for this patient population and reduce variability in clinical trial and study environments.